China Town as a multilingual workplace - Thomson, Miché (Stellenbosch Papers in Linguistics Plus, 2019)
Since the emergence of China within the BRIC[1]-group in 2001 (BRICS as from 2010), people of Chinese origin have gradually secured a market share in Africa that is successful at both formal and informal levels. A fitting example present at the informal level is the establishment of China Town stores and Chinese markets. These Chinese markets are characterised as a network of small, family-owned businesses which sell goods imported from China at competitive prices. This business model has become part of most towns and cities in Africa, with Chinese-owned stores featuring in lower- and middle-class areas. Overwhelmingly, the stores are managed by Chinese patrons who employ shop assistants of African migrant origin. Both groups have integrated themselves into specialised occupations, with the Chinese opening these (in)formal stores and the Africans working closely with them as shop assistants. The shopkeepers and their assistants speak different languages, but living and working in a multilingual South Africa, they communicate in English which is the common lingua franca. This research report presents an overview of an ongoing doctoral study which focuses on the Chinese markets in South Africa, with a specific interest in the nature of interaction between the Chinese shopkeepers and their African shop assistants. It seeks to describe and explain how language-in-interaction is performed or socially produced, where participants do not have a common first language, and English is the lingua franca. The data comprises audio recordings of the interaction between shopkeeper and assistants throughout the workday, as well as field note from observations of the research site. The ongoing study wishes to describe what happens linguistically when these different groups of migrants find themselves in new social and linguistic environments to which they acclimatise in profound ways. [1] BRIC: abbreviation for rapidly developing economies in Brazil, Russia, India and China, coined in 2001; in 2010 South Africa joined, so that then the group became “BRICS”.